Numerical Solutions for the Improved Korteweg De Vries and the Two Dimension Korteweg De Vries (2D KDV) Equations (Global Journal of Science Frontier Research, 2016)
In this paper we established a traveling wave solution by the ( -expansion method for nonlinear partial differential equations (PDEs).The proposed method gives more general exact solutions for two different types of nonlinear partial differential equations such as the improved Korteweg de Vries equation and the two dimension Korteweg de Vries (2D KdV) equations.
Keywords: the ( -expansion method; the improved korteweg de vries equation and the two dimension korteweg de vries (2D kdv)